Birth-related neonatal rib fracture: a case report - Van den Sande, Annelies; Gestels, Thomas; Van Damme, Karlijn; Trompenaars, Amanda (Belgian Journal of Paediatrics, 2023)
Rib fractures due to birth trauma are rare, other mechanisms of trauma need to be considered. We report the case of a large for gestational age newborn in the maternity ward with an isolated rib fracture due to birth trauma. Birth was complicated with shoulder dystocia after a vacuum extraction.